2019
DOI: 10.1210/clinem/dgz214
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation Between Telomere Attrition of Zona Fasciculata and Adrenal Weight Reduction in Older Men

Abstract: Context Although numerous theories are reported on sex differences in longevity, the underlying biological mechanisms remain unknown. We previously reported that telomere length in the zona reticularis cells of the human adrenal cortex was significantly longer in older than that in younger subjects. However, we could not evaluate sex differences in the telomere lengths. Objective To compare the telomere lengths of adrenocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Human adrenals harbor very low levels of telomerase activity. Despite this, older men (>65 years old) have significantly shorter telomere lengths in the zona fasciculata compared with the corresponding female subjects [ 78 ]. Telomere attrition in ageing men might contribute to the reduction in adrenal weight that is observed in this age group [ 78 ].…”
Section: Impact Of Gonadal Steroid Signaling In the Adrenal Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…Human adrenals harbor very low levels of telomerase activity. Despite this, older men (>65 years old) have significantly shorter telomere lengths in the zona fasciculata compared with the corresponding female subjects [ 78 ]. Telomere attrition in ageing men might contribute to the reduction in adrenal weight that is observed in this age group [ 78 ].…”
Section: Impact Of Gonadal Steroid Signaling In the Adrenal Cortexmentioning
confidence: 99%
“…Despite this, older men (>65 years old) have significantly shorter telomere lengths in the zona fasciculata compared with the corresponding female subjects [ 78 ]. Telomere attrition in ageing men might contribute to the reduction in adrenal weight that is observed in this age group [ 78 ]. Of note, zR displays the longest telomeres among the adrenocortical zones, and their length appears to increase rather than decrease with age [ 79 ].…”
Section: Impact Of Gonadal Steroid Signaling In the Adrenal Cortexmentioning
confidence: 99%
“…After peak growth, adrenal weight dramatically declined in males, but regressed at a slower rate in females. This trend is also observed in various mammalian models and human clinical samples where adrenal weight decreases in an aged setting and is accelerated in males [ 23 , 24 ]. Additionally, data from our own laboratory confirm that adult C57BL/6J female adrenals are larger when compared to that of males, and male adrenal weight significantly decreases with advanced aging up to 78 weeks [ 25 ].…”
Section: Structural Changes In the Aged Adrenalmentioning
confidence: 59%
“…A Japanese study measured telomere length, which is commonly shortened in senescent cells [ 112 ]. This study reported an unexpected age-associated increase in telomere length in the zR compared with the zG and zF, and also showed a modest increase in zR telomere length with age in males and females [ 24 , 113 ]. This is surprising given that cells of the zR are expected to be the longest-lived adrenal cortex cells and telomere lengthening is quite unusual.…”
Section: Senescencementioning
confidence: 99%
See 1 more Smart Citation